Estudo de alterações dimensionais da mandíbula medidas em radiografias panorâmicas - Carvalho, Antonio Augusto Ferreira [UNESP] (My University, 2010)
Rotational panoramic radiograpy is a widely used procedure for examination of the jaws. Then, the aim of this study was analyse the mandibular growth from images obtained on panoramic radiographs of male and female children with chronological age between 7-10 years old. Craniometrics points were identifyed and linear measurements obtained from mandibular body and ramus. The results showed an increase in mandibular body lenght and mandibular ramus height in both sexes. Statistically significant correlation was found between the total mandibular lenght (from codilion to mental) and mandibular body lenght (from gonion to mental), in male and female children.

O objetivo deste trabalho foi o de avaliar alterações dimensionais da mandíbula a partir das imagens de radiografias panorâmicas obtidas de aparelho Rotograph. Pontos craniométricos foram marcados nas imagens da mandíbula e medidas lineares foram obtidas de radiografias de crianças dos dois sexos, com idade cronológica entre 7 e 10 anos. As medidas realizadas mostraram que houve aumento significativo do comprimento do corpo e da altura do ramo da mandíbula. Houve significativa correlação entre o comprimento total da mandíbula (medido entre o condílio e um ponto na região inferior do mento) e comprimento do corpo (medido entre gônio e mento), tanto no sexo masculino quanto no feminino.
Study of mandibular dimensional changes measured on panoramic radiograph
Keywords: Panoramic radiography; Mandible; Radiografia panorâmica; Mandíbula